El concepto de desarrollo humano en las políticas sociales asistenciales del vaso de leche y los comedores populares, Peru- 1985 - 2008 - Huemura Paredes, Elba Sigghy Sonia (2012)
The present investigation evidences the relation between the Concept of Human Development in the Social Assistance Programs of the Glass of Milk and the Popular Dining Rooms, in the period 1985-2008. This investigation was made because of the following reasons: because both programs are directed to poor and vulnerable sectors where children and women are representative, bacause they both are National Programs and use more than 50% from the budget of the Programs of Alimentary Support, but without a nutritional impact; because been the most extended in the country and the most organized red of wome and because they are guided to impact in the nutrition that is an indicator of results of the Human Development. The historical, descriptive and analytic methods were used and as technique the analysis of documental bases and an instrument of control was applied to check the presence-absence of indicators of dimensions of the human development. The results evidenced a very low relationship between these programs and the Concept of Human Development. We concluded that both programs are not even singular satisfactors but pseudosatisfactors of the necessity of subsistence, because they don‟t provide foods that improve the nutritional levels. They do not provide opportunities and real capacities of auto subsistence and do not provide work, participation and freedom but as satisfactors inhibitors through the clientelism that alienates and blocks these fundamental necessities. They are no spaces of citizen socialization for women, children and young people; they maintain the orientation that the feeding is not a right but responsibility of the (OSB) base organizations which are considered belong to the sector of the social reproduction and not of the production.